2016
DOI: 10.1021/acsami.5b11325
|View full text |Cite
|
Sign up to set email alerts
|

Highly Transparent Wafer-Scale Synthesis of Crystalline WS2 Nanoparticle Thin Film for Photodetector and Humidity-Sensing Applications

Abstract: In the present investigation, we report a one-step synthesis method of wafer-scale highly crystalline tungsten disulfide (WS2) nanoparticle thin film by using a modified hot wire chemical vapor deposition (HW-CVD) technique. The average size of WS2 nanoparticle is found to be 25-40 nm over an entire 4 in. wafer of quartz substrate. The low-angle XRD data of WS2 nanoparticle shows the highly crystalline nature of sample along with orientation (002) direction. Furthermore, Raman spectroscopy shows two prominent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
152
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(156 citation statements)
references
References 45 publications
(54 reference statements)
3
152
0
1
Order By: Relevance
“…Because of their unique physicochemical properties, such as superior carrier mobility and high photoelectric conversion efficiency, two-dimensional (2D) materials have attracted attention to facilitate the performance improvement of photo detectors. [7] Transition-metal dichalcogenides (TMDs), such as MoS 2 , [8] MoSe 2 , [9] and WS 2 , [10] also have thickness-tunable bandgaps, [11] low dark currents, and relatively high carrier mobilities. For example, ultra-broadband photodetectors using graphene [4] have zero bandgaps with no switching characteristics.…”
mentioning
confidence: 99%
“…Because of their unique physicochemical properties, such as superior carrier mobility and high photoelectric conversion efficiency, two-dimensional (2D) materials have attracted attention to facilitate the performance improvement of photo detectors. [7] Transition-metal dichalcogenides (TMDs), such as MoS 2 , [8] MoSe 2 , [9] and WS 2 , [10] also have thickness-tunable bandgaps, [11] low dark currents, and relatively high carrier mobilities. For example, ultra-broadband photodetectors using graphene [4] have zero bandgaps with no switching characteristics.…”
mentioning
confidence: 99%
“…These 2D materials have shown attractive electronic properties for electronic device applications like OLED, optoelectronics, TFT and sensors2345. In recent years quasi 2D materials like WSe 2 , WS 2 , MoS 2 and MoSe 2 are under intensive research as they also have a unique potential to be used in nanotechnology and nanoscience for various applications.…”
mentioning
confidence: 99%
“…Furthermore, hot wire CVD technique was adopted to prepare WS 2 nanoparticles thin film. The size of as‐synthesized WS 2 NPs is estimated to be around 25 to 40 nm …”
Section: Synthesismentioning
confidence: 99%
“…The 0D TMDs‐based thin films show good response to humidity and good photosensitivity. It was found that the resistance of the films decreases with increasing relative humidity, while photonic‐sensitive current recovery also open up new opportunities for photodetection ( Figure a and b) …”
Section: Propertiesmentioning
confidence: 99%
See 1 more Smart Citation